The Influence of the Digital Economy and Women's Empowerment on the Family Economy - Nela Dharmayanti; Budiastuti Fatkar; Aisyah Ratnasari (Sawwa: Jurnal Studi Gender, 2022)
Women play an essential role in both the online and offline economies. As a result of digital era changes, women are more likely to innovate in the administration of small and medium-sized enterprises (SMEs). The purpose of this study is to determine how the growth of the digital economy and the empowerment of women have influenced the family economy. This investigation included SME communities in Tangerang, Banten. The sampling technique utilised is a hybrid of probability sampling and random sampling. They are compiling data through the use of a questionnaire. There is a 97-person on number of subjects whose data can be analyzed. This research uses Partial Least Squares (PLS) to analyze the data. The findings indicated that: 1) The digital economy construct has a positive and significant influence on women's empowerment (t=2.990); 2) Women's empowerment ha a positive and significant influence on the family economy (t=7.141); and 3) The digital economy and women's empowerment has a positive and significant influence on the family economy (F=242.61). Therefore, digital-based women’s economic empowerment is a means to increase the financial independence of a family and the economic growth of the community.